A century of East African raids: Anywa and Murle: Anywa and Murle - Yalew, Shimels Ayele (Ethiopian Journal of Social Sciences, 2024)
The recurring cross-border raids and counter-raids in the border areas of south-western Ethiopia and south-eastern Sudan have been considered as a recent phenomenon. However, the findings of this study, based on content analysis of archival sources, travelersâ€™ accounts, books, articles and unpublished secondary materials, suggest that the raids have historical roots and extend much farther than current trends. As a result, the raids and counter-raids between the Anywa and the Murle were caused by economic, political, geographical and cultural factors. There was a period of hegemony in the raids, one after the other. The Anywa were dominant in the first half of the 20th century, but the Murle rose to dominance from the 1950s onwards.  The raids have had an economic, political and social impact on the region.